In situ digestibility of corn stover’ treated with fibrolytic enzymes - López-Inzunza, Hugo de Jesús; Chongo-García, Bertha Bienvenida; La-O-León, Orestes; Guerra-Liera, Juan Eulogio; Luna-López, Maribel; Castro-Camacho, Samuel Jesús; López-Juárez, Luciano Abelino (Ciencia y Agricultura, 2017)
In situ digestibility of corn Stover fiber matrix treated with an enzymatic complex was studied by using two Swiss bulls (700 kg PV) with ruminant cannula. We used a randomized block design, where each animal constituted a block, and three enzyme levels: 0 g (TC), 1 g (T1), and 2 g (T2) of Fibrozyme® kg fodderl MS. The samples (5 g of dry matter in nylon bags) were incubated in the ruminant, and were extracted at 6, 12, 24, 48 and 72 hours after fermentation. Debasement was analyzed by a none lineal regression, using the P=a+b* (1-e-c* (t-to)) model. The soluble portion of the fibrous matrix, determined by washing the bags, resulted similar in both fiber fractions (FDN and FDA), with values of 0.50, 0.59 and 0.68 % respectively for each treatment. The degradability values of the insolvent, but degradable, fraction were: 37.28, 36.64 and 37.30 % for FDN, and 33.85, 35.07 and 41.19 % for FDA, with their three respective treatments. The T2 (FDN) and the TC (FDA) registered the highest degradation speed values (c %/h). The lag phase was approximately of 3.80, 4.90 and 4.80 h for FDN and 5.30, 5.30 and 4.90 h for FDA, with their three respective treatments. The FDN effective degradability (DE) oscillated between 19.70-14.40, 21.30-15.90 and 22.10-16.60 %; and the FDA, between 20.30-15.30, 21.10—15.80 and 23.40-17.30 %, in each one of the treatments, by using different ruminant exchange constants. The corn stover showed good degradation potential, over 39 % in FDN and 44 % in FDA, when treated with the highest levels of fibrolytic enzymes (T2). The results showed that an optimal usage of the fiber-matrix as energy source for the animal can be achieved, when enzymatic complexes are used in agriculture products and residues such as corn stover through its ruminal fermentation.